Central banks: From overburdening to decline? - Otmar Issing (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
"Institutional Overburdening" to a large extent was a consequence of the "Great Moderation". This term indicates that it was a period in which inflation had come down from rather high levels. Growth and employment were at least satisfying and variability of output had substantially declined. It was almost unavoidable that as a consequence expectations on future actions of central banks and their ability to control the economy reached an unprecedented peak which was hardly sustainable. Institutional overburdening has two dimensions. One is coming from exaggerated expectations on what central banks can achieve ("expectational overburdening"). The other dimension is "operational overburdening" i.e. overloading the central bank with more and more responsibilities and competences.
urn:nbn:de:hebis:30:3-416923
Keywords: 330; Central Banking; ECB; Monetary Policy